2020
DOI: 10.1038/s41598-020-70958-3
|View full text |Cite
|
Sign up to set email alerts
|

Sharing and caring: Testosterone, fathering, and generosity among BaYaka foragers of the Congo Basin

Abstract: Humans are rare among mammals in exhibiting paternal care and the capacity for broad hyper-cooperation, which were likely critical to the evolutionary emergence of human life history. In humans and other species, testosterone is often a mediator of life history trade-offs between mating/competition and parenting. There is also evidence that lower testosterone men may often engage in greater prosocial behavior compared to higher testosterone men. Given the evolutionary importance of paternal care and heightened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The Cronbach's alphas for these peer rankings ranged from 0.76 to 0.86, indicating relatively strong internal reliability [13]. The sub-set of BaYaka fathers who provided the rankings (n = 21) did not significantly differ from the fathers who did not rank their peers but who had ranking data (n = 10) for any key study variables [32].…”
Section: (C) Bayaka Fathering and Ranking Datamentioning
confidence: 95%
See 1 more Smart Citation
“…The Cronbach's alphas for these peer rankings ranged from 0.76 to 0.86, indicating relatively strong internal reliability [13]. The sub-set of BaYaka fathers who provided the rankings (n = 21) did not significantly differ from the fathers who did not rank their peers but who had ranking data (n = 10) for any key study variables [32].…”
Section: (C) Bayaka Fathering and Ranking Datamentioning
confidence: 95%
“…We chose to measure cortisol via fingernails because BaYaka individuals generally keep their hair cut very close to the scalp, particularly for men and boys, which made nail sampling a better cultural fit in this setting. Moreover, though we have drawn on saliva sampling at this site [31,32], we did not have the research infrastructure to collect multiple saliva samples across the day, repeated across multiple days, for each participant, as is recommended for assessment of trait-like individual cortisol profiles, and to then freeze that large volume of samples on site during fieldwork [36]. After shipment to Dr Jerrold Meyer's laboratory at the University of Massachusetts-Amherst, the nail samples were analysed for cortisol using a commercially available kit (Arbor Assays; Ann Arbor, MI; no.…”
Section: (F ) Fingernail Cortisolmentioning
confidence: 99%
“…Second, we expect gender to be an important determinant of compliance with protective health measures and to interact with marriage. Men tend to score lower than women on prosocial scales (e.g., Andreoni and Vesterlund, 2001 , Croson and Gneezy, 2009 ), and married men and fathers tend to be more altruist and prosocial than single or childless men ( Gettler et al, 2020 , Gray and Campbell, 2009 ), whether due to selection (i.e., men with prosocial traits are more likely to get married and have children) or adaptation (i.e., men adjust their values after they get married and have children). Therefore, we expect men to be less compliant with protective health measures against COVID-19, but to a lesser extent if they are married.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, human fathers’ flexible psychobiological responses to partnering and parenting are thought to reflect the importance of paternal care in the evolutionary past, with psychobiological mechanisms helping divert fathers’ limited resources (e.g., time and energy) towards parenting effort (Gettler, 2014, 2016; Gray et al, 2017; Rosenbaum & Gettler, 2018; Storey & Ziegler, 2016). For example, in societies in which fathers commonly engage in cooperative caregiving, fathers with lower testosterone have been found to engage in greater direct caregiving, to spend more time in close proximity to their children, including during sleep (cosleeping), and to have less conflict with their partners compared to higher testosterone fathers (Gettler, 2016; Gettler et al, 2020; van Anders, 2013). Paralleling earlier cross‐sectional studies (e.g., Gray et al, 2002, 2004), longitudinal research has shown that in these societal contexts men experience biologically‐meaningful declines in testosterone as they transition to parenthood, on average.…”
Section: Introductionmentioning
confidence: 99%